2005
DOI: 10.1002/rcm.1795
|View full text |Cite
|
Sign up to set email alerts
|

A selective unsaturated hydrocarbon subtraction technique for stable carbon isotopic analysis of atmospheric methyl chloride, methyl bromide, and C2C5 saturated hydrocarbons using continuous‐flow isotope ratio mass spectrometry

Abstract: Using continuous-flow isotope ratio mass spectrometry, we have developed a new analytical system which enables us to determine the stable carbon isotopic composition of CH3Cl, CH3Br, and C2-C5 saturated hydrocarbons in gas samples even if they contain substantial amounts of unsaturated hydrocarbons, using an I2O5 reagent for their selective subtraction. The analytical precision of the delta13C determinations is better than 0.5 per thousand for >300 pmolC injections and better than 5 per thousand for 20 pmolC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Indeed, the δ 13 C values of i‐butane emitted from the combustion of C3 plants showed the most 13 C‐depeleted value in our experiments, irrespective of fuel materials. These results correspond with previous studies,1, 6 but the large isotopic fractionation of i‐butane, as seen in the combustion of maize, was not observed in C3 plant burning. Furthermore, the observed large 13 C depletion is not common to compounds with branched structures (i‐pentane did not show such a large 13 C depletion).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the δ 13 C values of i‐butane emitted from the combustion of C3 plants showed the most 13 C‐depeleted value in our experiments, irrespective of fuel materials. These results correspond with previous studies,1, 6 but the large isotopic fractionation of i‐butane, as seen in the combustion of maize, was not observed in C3 plant burning. Furthermore, the observed large 13 C depletion is not common to compounds with branched structures (i‐pentane did not show such a large 13 C depletion).…”
Section: Resultssupporting
confidence: 92%
“…Since the development of the stable carbon isotopic measurement system for atmospheric C 2 –C 5 non‐methane hydrocarbons (abbreviated as NMHCs) using gas chromatography/combustion furnace/isotope ratio mass spectrometry (GC/C/IRMS) by Rudolph et al .,1 several isotopic studies of atmospheric NMHCs have demonstrated that isotopic measurement can potentially be a valuable tool for the estimation of their sources, sinks and distributions 2–5. Recently, a few isotopic datasets have become available relating to major emission sources of NMHCs,1, 4, 6, 7 and to the kinetic isotope effects associated with atmospheric degradation processes 3, 8, 9. It would, however, be premature to determine a representative isotopic signature from a limited number of measurements.…”
mentioning
confidence: 99%
“…The estimates of burned plant composition by Randerson et al (2005) do not consider the potential kinetic isotope effects that may escort biomass burning emission for various tracers. Czapiewski et al (2002) and later Komatsu et al (2005) and Nara et al (2006) report that δ 13 C of the major NMHCs emitted from biomass burning generally follows that of the fuel burnt, and the measurements did not reveal significant additional fractionations associated with the formation processes. Consequently, here (and further for the GFED data) the 13 C isotope fractionation escorting burning process is assumed to be negligible.…”
Section: For Details)mentioning
confidence: 83%
“…To determine the δD values of nanomolar quantities of H 2 , we purified H 2 using multi‐step gas chromatographic separations and then introduced the H 2 directly into the CF‐IRMS system (Delta‐V, Thermo Fisher Scientific, Waltham, MA, USA) at Hokkaido University (Hokkaido, Japan) . Figure shows the schematic design of the entire analytical system.…”
Section: Methodsmentioning
confidence: 99%